Obtaining the Maximum Loading Point of Electric Power Systems using the Decoupled Methods of Newton - Bonini Neto, A. [UNESP]; Magalhaes, E. M.; Alves, D. A. [UNESP] (Ieee-inst Electrical Electronics Engineers Inc, 2016)
This paper presents a proposed Newton decoupled method modification (simultaneous resolution algorithm and alternate) with the addition of an equation line passing through of a point in the plane determined by the variables: loading factor and the nodal voltage magnitude of a bus k. The use of this parameterization technique eliminates the singularity of Jacobian matrix and all the consequent problems of illconditioning, increasing also the group of voltage variables that can be used as parameter and therefore, obtain the complete tracing of P-V curves and the maximum loading point of electric power systems. Another important factor that will be presented in this paper is the reduction of the CPU time that the decoupled methods provide. A comparison of the simultaneous and alternate resolution schemes will be presented.
Keywords: Continuation method; Decoupled load flow; Parameterization techniques; Maximum loading point; P-V curve